Development of Augmented Reality Application As A Mathematics Learning Media In Elementary School Geometry Materials - Dinayusadewi, Ni Putu; Agustika, Gusti Ngurah Sastra (Universitas Pendidikan Ganesha, 2020)
The problem of this research is the lack of interactive learning media on elementary school geometry which makes it difficult for students to understand the explanation that conveyed by the teacher. This research aims to design geometrical mathematics learning media especially cubes and blocks based on Augmented Reality technology for fifth-grade elementary school students and to know the level of product worthiness from the subject and validator. The development process of this research consists of five steps like Analysis, Design, Development, Implementation, and Evaluation. The data collection method used was a closed questionnaire. The results of the research questionnaire were analyzed using a Likert scale analysis, so the following results are obtained: The results trial of the material expert validator showed a percentage of 92.50% which is included in the excellent category with very decent information. Media design expert validator with a percentage of 93.00% which is included in the excellent category with very decent information. Product response of three elementary school teachers with a percentage score of 89.33% included in the very good category. Product responses of fifteen elementary school students with a percentage score of 83.73% with a very good category. It was concluded that the application of elementary geometrical mathematics learning media based on Augmented Reality technology can be used in elementary schools as a medium for learning mathematics.